Moderasi Beragama Nahdlatul Ulama dan Muhammadiyah dalam Konsep Islam Nusantara dan Islam Berkemajuan - Nasikhin Nasikhin; Raharjo Raaharjo; Nasikhin Nasikhin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
This study aims to determine the religious moderation teachings of Nahdlatul Ulama (NU) and Muhammadiyah in the concepts of Nusantara Islam and Progressive Islam and their relation to the verses of the Qur'an. The type of research is literature study with a qualitative approach that describes and analyzes library data, in the form of books, journals, magazines, and news relevant to the research theme. The results showed that; first, the teachings of religious moderation in NU are illustrated through the jargon of Islam Nusantara, while Muhammadiyah is through Progressive Islam. Second, the alternation of religious moderation between NU and Muhammadiyah is related to the Koranic verse, namely they both uphold an attitude of peace (Al Baqarah: 143), help each other (Al-Maidah: 2), and obey the leader (Annisa 59). Third, the symbol of religious moderation of NU and Muhammadiyah is more directed to pluralistic values ​​that are in accordance with the context of Islam in Indonesia which is plural so that it does not conflict with the contents of the QS. Al-Hujurat Paragraph 13. This research can be used as a means of expanding views so that people think more intelligently and clearly, and avoid acts of violence that are very contrary to Wasathiyah values.